Intravoxel incoherent motion imaging measurement of perfusion changes in the parotid gland provoked by gustatory stimulation: A pilot study. Issue 2 (19th July 2016) - Becker, Anton S.; Manoliu, Andrei; Wurnig, Moritz C.; Boss, Andreas
Abstract : Purpose: To demonstrate the feasibility of intravoxel incoherent motion imaging (IVIM) for quantification of perfusion changes in the parotid gland after gustatory stimulation. Materials and Methods: Eight healthy volunteers underwent diffusion‐weighted magnetic resonance imaging (MRI) of the neck at 3T with 11 dynamic acquisitions (9 b‐values between 0 and 980 s/mm 2, 2:40 min each). After 5:20 minutes, a lemon‐mint‐drop was administered orally. Perfusion fraction (Fp ), pseudodiffusion (D*), tissue diffusion (Dt ) coefficients, and optimal b‐value threshold were measured using a multistep variable b‐value threshold fitting approach. Dynamic changes in the coefficients between three exemplary timepoints (baseline, after stimulation, after dissolution) were compared using a Mann–Whitney U ‐test with Bonferroni correction ( P < 0.016 significance level). Results: Mean values (95% confidence interval [CI]) for IVIM parameters at baseline were Fp : 0.11 (0.08–0.15), D*: 56.48 mm 2 /s (39.71–98.27), Dt : 1.01 mm 2 /s (0.84–1.06), b‐value threshold: 30 s/mm 2 (21.25–105). After stimulation: Fp 0.16 (0.15–0.24; P < 0.01), D* 93.83 mm 2 /s (77.98–129.53, P = 0.25), Dt 0.93 mm 2 /s (0.87–1.08, P = 0.94), b‐value threshold 20 s/mm 2 (13.75–26.25 s/mm 2, P = 0.10), reflecting the increase in tissue perfusion. After dissolution of the drop: Fp : 0.13 (0.11–0.18, P = 0.38), D*: 101.61 mm 2 /s (90.68–144.55, P = 0.07), Dt : 0.91 mm 2 /s (0.85–1.05, P = 0.64), b‐value threshold: 15 s/mm 2 (11.25–40, P = 0.38). Conclusion: The IVIM method allows for simultaneous quantification of changes in perfusion and diffusion effects after gustatory stimulation of the parotid gland. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:570–578.